PENERAPAN MEDIA PEMBELAJARAN GAMIFIKASI GAME WORDWALL UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS IV UPT SPF SDN MANNURUKI KECAMATAN TAMALATE KOTA MAKASSAR - Sarif Hidayatullah S; Aliem Bahri; Ummu Khaltsum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low reading skills of fourth-grade students at the SPF Unit of Mannuruki Elementary School Tamalate District Makassar City, as indicated by student learning outcomes that had not yet reached the minimum mastery criteria. One factor contributing to this problem was the limited use of interactive and engaging learning media, which affected students’ learning motivation. This study aimed to improve students’ reading skills through the implementation of gamification-based learning media using the Wordwall game in Indonesian language learning.This research employed Classroom Action Research conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were 28 fourth-grade students at the SPF Unit of Mannuruki Elementary School. Data were collected through observation, tests, and documentation. Data analysis was carried out using descriptive quantitative and qualitative methods.The results showed that the use of Wordwall media improved students’ reading skills. In Cycle I, the average student score reached 69 with a mastery percentage of 57%. In Cycle II, the average score increased to 86 with a mastery percentage of 89%. Therefore, the gamification-based Wordwall learning media is effective in improving the reading skills of fourth-grade elementary school students.